Dinamika Kesejahteraan Psikologis pada Perempuan Dewasa Awal yang Mengalami Kekerasan Emosional dalam Hubungan Pacaran - Yunanto, Taufik Akbar Rizqi; Kenward, Bryan (Jurnal Online Psikogenesis, 2024)
The phenomenon that emotional violence is considered as "ordinary love disputes" so that it naturally occurs and is misinterpreted as a form of love is a cause for concern. Research has found that emotional abuse has the most damaging and painful effects because it directly attacks a person's core self-esteem, creating more lasting wounds than other forms of abuse. Early adult women are vulnerable to experiencing emotional abuse because they are in search of meaning and purpose in life through interpersonal relationships based on trust and are in a phase of forming romantic relationships. This research aims to understand more deeply about the description and dynamics of psychological well-being in early adulthood, especially in women who experience emotional abuse in dating relationships. The design used in this study is qualitative with an interpretive phenomenological approach. The criteria set by the researchers in this study were women who were in the early adulthood stage (18-40 years) who had experienced emotional abuse in dating relationships with a total of two participants involved in this study. The results of the analysis found that emotional abuse affects the level of psychological well-being of the two participants. The low level of psychological well-being that participants experience when experiencing emotional abuse makes it difficult to get out of the cycle of emotional abuse in the dating relationship. The uniqueness found by researchers is that the influence of distance or differences in domicile between participants and partners is a factor in helping participants to escape emotional abuse in the dating relationship.